An exploration of teacher perceptions and actions to conserve wetlands in Kenya - Ndaruga, Ayub Macharia (Rhodes University, Faculty of Education, Department of Education, 2004)
This thesis presents the findings of an exploration of teacher perceptions and actions to conserve wetlands in Kenya. It reports findings of a case study survey done with 54 primary school teachers from seven of eight Kenyan provinces. The teachers were sampled from a larger group of 242 teachers who participated in an in-service course on wetlands conservation. The in-service course engaged teachers in exploring various aspects of wetlands and how they could enhance their conservation using both formal and non-formal contexts. The survey approach was used in the research and was augmented with a reflective process. Survey tools used were the questionnaires and interviews. The reflective process entailed observation, document analysis, field notes and the researcher's diary. Research data was analysed in several stages. The study revealed that teachers were users of local wetlands just like other members of their communities. The teachers differed among themselves with respect to their perceptions of the value and threats to their local wetlands. The teachers also differed in their perceptions of community awareness of their local wetlands. The teachers' perceptions about environmental education and wetlands were not holistic. The teachers recorded various opportunities to foster wetlands conservation in their local contexts at school and the community. These were their fellow teachers, the pupils, the subjects taught, clubs, environmental days and the community. The relative importance of these opportunities differed among the teachers. Many teachers claimed being motivated to promote wetlands conservation using both formal and non-formal contexts. Their motivation was based on diverse aspects of wetlands, education and the in-service training they attended in 1999. However, the intensity of motivation differed for each aspect. For instance, at community level in-service training was a major motivator while the curriculum aspects were not mentioned at all. Teachers reported having involved their pupils and the community in several activities to conserve the local wetlands. These activities seemed to be dominated by theoretical approaches, eco-management activities and visits to wetlands. There was little evidence to indicate the teachers being engaged in addressing the implications for sustainability of the perceived local wetland values and threats. The activities reported also failed to show engagement with local environmental problems as a deliberate proactive process involving exploration, discussion, action taking and reflection. Most of the activities were presented as one off activities rather than as a cyclic continuously improving series of interventions. The overall scenario presented by the teachers is one of inadequacy in addressing the sustainable use of wetlands. Teachers suggested various constraints that affect their realisation of environmental education for wetlands sustainability. The constraints traverse various aspects of the economic, biophysical, political, educational and social aspects of wetlands conservation. The study suggested the need for teachers to treat their contextual and personal conceptions as problematic rather than as simplistic or linear issues and to formulate ways to address them. This study suggests a potential but under-utilised opportunity to promote wetlands sustainability. The overall picture generated by the data in this study is a need to consider wetland training for teachers that integrates the holistic aspects of wetlands as well as the environmental education for sustainability perspectives grounded in local contexts.
Keywords: Wetlands -- Kenya; Wetland conservation -- Kenya; Wetland conservation -- Kenya -- Study and teaching ( Elementary); Wetlands -- Kenya -- Study and teaching (Elementary); Environmental education -- Kenya; Sustainable development -- Study and teaching (Elementary) -- Kenya